Multistep pathogenesis of chronic myelomonocytic leukemia in patients. (23rd March 2022) - Geissler, Klaus; Jäger, Eva; Barna, Agnes; Gurbisz, Michael; Marschon, Renate; Graf, Temeida; Nösslinger, Thomas; Pfeilstöcker, Michael; Machherndl‐Spandl, Sigrid; Stauder, Reinhard; Zebisch, Armin; Sill, Heinz; et al.
Abstract: Background: A multistep pathogenesis of myeloid leukemia including mutations in epigenetic, spliceosome, and signaling genes has been recently demonstrated in a preclinical model but is poorly validated in patients. Methods: Clinical, phenotypic, and biologic features were compared between three distinct molecularly defined CMML cohorts including TET2 monomutated patients (T, n = 10), TET2 / SRSF2 bimutated patients (TS, n = 19), and patients who had NRAS mutations in addition to TET2 / SRSF2 comutations (TSN, n = 14). Results: Median survival was 90, 45, and 9 months, respectively ( p = .001). Whereas no patient in the T and TS group transformed into acute myeloid leukemia (AML), 6/14 patients in the TSN group had AML at study entry or transformed during follow‐up. Leukocyte counts, blast cell counts, and LDH levels were significantly higher in TSN vs. TS and T, respectively, whereas hemoglobin and platelet values were not significantly different. Increased growth factor‐independent myeloid colony formation was restricted to TSN but not found in T and TS, respectively. The proportion of patients showing in vitro myelomonocytic skewing in T, TS, and TSN was 0%, 56%, and 100%, respectively ( p = .010). Conclusion: Our results demonstrate that the model of multistep pathogenesis in CMML can be recapitulated in patients regarding clinical, phenotypic, and biologic features.